Holocene precipitation seasonality in northern Svalbard: Influence of sea ice and regional ocean surface conditions - Kjellman, Sofia Elisabeth; Schomacker, Anders; Thomas, Elizabeth K.; Håkansson, Lena; Duboscq, Sandrine; Cluett, Allison; Farnsworth, Wesley R.; Allaart, Lis; Cowling, Owen; McKay, Nicholas P.; Brynjólfsson, Skafti; Ingólfsson, Ólafur (Quaternary Science Reviews, 2020)
Arctic precipitation is predicted to increase in the coming century, due to a combination of enhanced northward atmospheric moisture transport and local surface evaporation from ice-free seas. However, large model uncertainties, limited long-term observations, and high spatiotemporal variability limit our understanding of these mechanisms, emphasizing the need for paleoclimate records of precipitation changes. Here we use lipid biomarkers in lake sediments to reconstruct precipitation seasonality in northern Spitsbergen, Svalbard. We measured the hydrogen isotopic ratios (δ 2 H) of n -alkanoic acids (C 20 –C 30 ) from sedimentary leaf waxes in lake Austre Nevlingen, Spitsbergen. We interpret δ 2 H values of mid-chain (C 22 ) and long-chain (C 28 ) n -alkanoic acids to represent δ 2 H of lake and soil water, respectively. Austre Nevlingen lake water δ 2 H reflects amount-weighted mean annual precipitation δ 2 H. In contrast, soil water is mostly recharged by summer rainfall, and therefore reflects δ 2 H values of summer precipitation. Austre Nevlingen leaf wax δ 2 H values are 2 H-depleted in the Early Holocene, suggesting high winter precipitation amounts. This coincides with high summer insolation, strong Atlantic water advection and reduced spring sea-ice cover in surrounding waters. Winter precipitation continued to dominate until c. 6 cal. kyr BP. After 6 cal. kyr BP, the trend in the biomarker record is not as clear. This could be related to colder conditions causing longer duration of seasonal lake-ice cover, thereby influencing the precipitation seasonality registered by the lake water. The Austre Nevlingen record suggests a close relationship between precipitation seasonality and regional ocean surface conditions, consistent with simulations suggesting that Arctic winter sea-ice loss will lead to increased local evaporation.